Effects of maternal obesity on early and long-term outcomes for offspring - Stirrat LI; Reynolds RM (Dove Medical Press, 2014)
Laura I Stirrat,1,2 Rebecca M Reynolds2,3 1Medical Research Council Centre for Reproductive Health, Queens Medical Research Institute, University of Edinburgh, Edinburgh, UK; 2Tommy's Centre for Maternal and Fetal Health, Queens Medical Research Institute, University of Edinburgh, Edinburgh, UK; 3Endocrinology Unit, University/British Heart Foundation Centre for Cardiovascular Science, Queens Medical Research Institute, University of Edinburgh, Edinburgh, UK Abstract: The prevalence of maternal obesity has increased significantly in recent years, and obesity is currently the most common comorbidity of pregnancy. Pregnancies of obese women are often defined as "high-risk" for the purposes of clinical care, with many well documented risks to the mother and developing baby. Maternal physiology and metabolism is dysregulated in the context of obesity, which may contribute to some of the adverse outcomes during pregnancy. Furthermore, maternal obesity has been hypothesized to cause harmful effects for the developing baby through "early life programming." This review will examine evidence from human studies for outcomes of offspring from obese women during pregnancy, during labor, during the neonatal period, and later in life. Keywords: pregnancy, short-term, physiology, metabolism, early life programming, neonatal complications, adverse intrauterine environment